Muhammad Husein's Gender Perspectives on Inheritance in Mukomuko Customary Law - Dwi Putra Jaya; Laras Shesa (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2024)
This research examines the transmission of the Mukomuko custom according to Muhammad Husein's perspective on gender studies, which posits that women possess equal status and responsibilities as males. This research aims to analyze the correlation between gender studies, as proposed by Muhammad Husein, and the inheritance system outlined in Mukomuko customary law. This research uses a normative juridical legal method using a statutory and conceptual approach. Data processing uses inductive techniques that describe the specifics of the Mukomuko traditional heritage in the study of Islamic law with a gender approach by Muhammad Husein. Data collection techniques are based on literature originating from previous research, which will later be analyzed by comparing the two inheritance studies. Data-gathering approaches rely on prior studies' literature, which will be analyzed by comparing the two inheritance studies. Research findings indicate that women benefit more economically from the Mukomuko custom's inheritance than men. In Mukomuko culture, the inheritance system gives priority to the maternal bloodline. According to Muhammad Hussein's gender perspective, it is important to note that this viewpoint does not align with Islamic law, as male body parts are not considered to be offered as gifts. As per Muhammad Hussein, the gender ratio is equal, with an even distribution of males and women. Muhammad Hussein's viewpoint demonstrates that Islam strongly values equality among all groups. The Quran unequivocally affirms the equality of all human beings in the eyes of Allah, with the sole distinguishing factor being their level of devotion